EFEKTIVITAS PEMBERIAN REBUSAN JAHE DAN AIR PERASAN JERUK NIPIS MADU TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER I DI PMB R DI PANDEGLANG TAHUN 2024 - Fazriah, Tiara Nurul; Febriyani, Putri Agus (SINERGI : Jurnal Riset Ilmiah, 2025)
Nausea and vomiting are one of the discomforts experienced by pregnant women in the first trimester which occurs in almost 50% of pregnant women. Nausea and vomiting that occurs continuously can cause dehydration and even weight loss in pregnant women and have bad consequences for pregnant women and the fetus. Non-pharmacological methods can be used as one of the efforts that can be done to reduce nausea and vomiting, one of which is ginger decoction and lime juice. The purpose of this study was to determine the Effectiveness of Giving Ginger Decoction and Lime Juice with Honey on Nausea and Vomiting in Pregnant Women in the First Trimester at PMB R Pandeglang in 2024. This type of research uses a case study conducted for 7 days. In this study, the sampling selection was carried out using the simple purposive sampling method with a sample size of 2 people. The results of this study indicate that there was a decrease in the degree of emesis gravidarum in the intervention of ginger decoction and lime juice from the 2nd visit with moderate emesis gravidarum, then decreased at the 3rd visit to mild. In conclusion, there is a comparison of the decrease in the frequency of nausea and vomiting in respondents with the intervention of ginger decoction with lime juice with honey. It is hoped that health workers will increasingly develop natural methods to overcome complaints in pregnant women